Jornalismo local: estudo da história profissional de jornalistas de São Félix do Xingu e Canaã dos Carajás, na Amazônia Oriental (Revista Internacional de Folkcomunicação, 2022)
The research is dedicated to systematizing the communication processes in the cities of São Félix do Xingu, Canaã dos Carajás and their surroundings, in the southeastern region of Pará, through the use of interviews and oral history. The exploratory investigation aims to describe and categorize the communication processes and the local communication of the mentioned region, based on the following categories: 1- journalistic structure, 2- professional organization of the company and/or institution of the third sector, 3- profile of the journalists' performance, 4- journalistic pro-duction - type, format and genres, 5- audience and periodi-city, 6- local salience and 7- information thematization. As a result, the mapping of communication processes and memories of local communicators who collaborate with the production of informational content in these cities is systematized.
Keywords: Local communication; São Félix do Xingu; Canaã dos Carajás; Oral History; Eastern Amazon